High-efficiency cucurbit[7]uril capillary column for gas chromatographic separations of structural and positional isomers. Issue 42 (13th April 2016) - Zhang, Yan; Qi, Meiling; Fu, Ruonong
Abstract : The CB7–OV capillary column by incorporation of CB7 into OV-210 achieved extremely high column efficiency and outstanding resolving performance for various types of structural and positional isomers. Abstract : Here we report the first example of cucurbit[7]uril (CB7) diluted in trifluoropropylmethylpolysiloxane (OV210) as the binary stationary phase (CB7–OV) for high-resolution gas chromatographic (GC) separations. The as-fabricated CB7–OV capillary column achieved extremely high column efficiency of 4660 plates per m. This is the highest column efficiency ever reported for cucurbit[ n ]urils for GC separations. Most importantly, the CB7–OV column exhibited superior selectivity and resolving ability for structural and positional isomers covering apolar to polar analytes, showing advantages over the neat CB7 and OV210 columns. Moreover, it showed good column repeatability and reproducibility with RSD values of 0.01–0.09% for run-to-run and 0.03–0.47% for day-to-day, and 2.9–5.2% for column-to-column, respectively, and column thermal stability up to 260 °C. The established highly-efficient strategy promotes taking full advantage of cucurbit[ n ]urils as GC stationary phases and may also be feasible for other advanced materials in separation science.